Identification and screening of active components from Ziziphora clinopodioides Lam. in regulating autophagy. Issue 17 (2nd September 2019) - Zhang, Xuan-Ming; An, Dong-Qing; Guo, Long-Long; Yang, Ning-Hui; Zhang, Hua
Abstract: This study investigated the flavonoid constituents of a traditional Chinese medical plant Ziziphora clinopodioides Lam. by using ultra-performance liquid chromatography coupled with quadruple time-of-flight mass spectrometry and screened the active components in regulating autophagy.Normal rat kidney (NRK) cells transfected with green fluorescent protein- microtubule-associated protein 1 light Chain 3(GFP-LC3) were treated with Z. clinopodioide s flavonoids and its chemical compositions. After 4 h of treatment, the auto-phagy spot aggregation in NRK cells was photographed and observed by laser scanning confocal microscopy. The following 10 flavonoid components of Z. clinopodioides were identified: baicalein(1), quercetin(2), hyperoside(3), quercetin3-O-β-d -glucopyranoside(4), apigenin(5), kaempferol(6), chrysin(7), diosimin(8), linarin(9) and rutin(10). Among these flavonoids, chrysin, apigenin and quercetin were identified as the active principles in activating autophagy. This research may provide a reference for further developing and utilizing Z. clinopodioides. Abstract :